Penguatan Literasi Agama sebagai Pembentukan Karakter Religius di SD Aisyiyah Kota Malang - Cahayaningsih, Ica Putri; Rossidy, Imron (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Literacy is the axis of efforts to improve the quality of human life. Therefore, literacy is the axis of the educational vortex. Literacy ability has a very important role and is a demand for skills needed in the 21st century. Through a broad understanding of existing sources of knowledge, it makes a person more introspective and chooses various positive values and practices them as a means of self-actualization in everyday life. Positive character can be formed through habituation from an early age so that applying religious literacy in elementary schools can be one of the efforts in shaping student character. This research uses a qualitative approach (qualitative reaserch), with a type of case study research. Data collected in this study through interview, observation, and documentation techniques. While the data analysis used is by collecting data, presenting data, condensing data and drawing conclusions / verification. The results of this study show that activities to strengthen religious literacy as a shaper of religious character have run well. This can be seen from several stages carried out, namely 1) habituation to reading 15 minutes before learning; 2) environmental development from physical, social, affective aspects and 3) learning in the classroom which is carried out in several stages, namely: reading, writing, listening and speaking which is carried out well at school. Meanwhile, there are also several supporting and inhibiting factors of the maximum achievement target of the religious literacy movement.